Homestay Management System - Tan, Yong Chuen; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2024)
The study centers on a Homestay Management System designed for owners to effectively oversee their accommodations. This web-based system aims to streamline homestay operations, offering features like property listing, reservation management, guest communication, user management and also overall system setting. With capabilities such as automated notifications and maintenance scheduling, the system provides a comprehensive platform. Focused on enhancing the guest experience, it empowers property owners to optimize their accommodations. The Homestay Management System serves as a valuable tool for hosts, centralizing tasks and facilitating efficient property management to maximize their property's potential.